2006
DOI: 10.1007/s11110-006-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the long-term variability of hydrophysical characteristics of the Black Sea based on the assimilation of the climatic hydrological fields L and altimetry data

Abstract: 551.465To study the long-term variability of the thermohaline and dynamic characteristics of the Black Sea, we use three versions of climatic fields, namely, the fields reconstructed in the model according to the old (1903-1982) and new (1903-2003) hydrological climatic data arrays of temperature and salinity and according to the data of satellite altimetry. The analysis of the altimetry-based climatic fields confirms the distinctions (established earlier according to the old and new data arrays) in the seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The circulation modeling performed using assimilation of climatic hydrological fields reconstructed from the modern dataset of 1903-2003 allowed revealing slight rise of the principal pycnocline in the winter-spring period (about 5 m) and MBSC intensification compared with the data of 1903-1982 [12,16].…”
Section: Introductionmentioning
confidence: 98%
“…The circulation modeling performed using assimilation of climatic hydrological fields reconstructed from the modern dataset of 1903-2003 allowed revealing slight rise of the principal pycnocline in the winter-spring period (about 5 m) and MBSC intensification compared with the data of 1903-1982 [12,16].…”
Section: Introductionmentioning
confidence: 98%
“…At present, there are numerous works devoted to the long-term and seasonal variations of the dynamics of its waters (see, e.g., [5][6][7][8][9][10][11][12][13]). It is shown that the eddy wave processes on synoptic scales (with typical sizes from ten to several tens kilometers and time scales from weeks to months) are observed in the upper 100-m layer in all seasons and characterized by significant space-and-time intermittence [6,[8][9][10]13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the available arrays of climatic data on the temperature and salinity of waters in the Black Sea [1], we can mention the appearance of a new climatic database of monthly average fields of dynamic sea level [2]. These fields and the corresponding fields of temperature and salinity were obtained as a result of the assimilation of the data of altimetry measurements for 1992-2003 in the model [3].…”
Section: Introductionmentioning
confidence: 99%
“…In [2], it is shown that, parallel with the climatic thermohaline fields, the climatic altimetry fields also contain the data on the long-term variations of hydrophysical characteristics of the Black Sea. This is why a procedure of joint assimilation of the climatic hydrological temperature and salinity fields and the fields of climatic altimetry level in a dynamic model of the sea was proposed in [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation